Design and planning of housing and neighbourhoods for elderly women - Datlen, Barbara M. (Truro , Nova Scotia, Canada Department of Humanities, Nova Scotia Agricultural College, 1995)
In the design and planning of housing and neighbourhoods for elderly women, it is essential for the professionals to recognize that the living environment is far more than just shelter. The living environment is a complex interrelationship of many factors, which include not only the physical, or built environment, but also the social and psychological perceptions of the milieu, and the impact of local state, federal and administrative policies.
Rural Studies Working Papers No. 14
Keywords: Housing for elderly women